PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR PENGUKURAN KINERJA - Mulyati, Yulia Sri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Qualitative descriptive method is applied in this research by performing data collection technique through questionnaires, documentation, observation, and interview.The result of this research indicates that the company performance from: (1) financial prespective is quite well since the ROI has undergone improvement for the last two years; (2) customer perspective in general has already in appropriate with the expectation, it can be seen from the customersâ prespective level and the customers and employees satisfaction are quite good; (3) In the internal business process prespective a description is obtained that PT Aweco Indosteel Perkasa Surabaya is in the production process of its products effectively, but it is inefficient from the analysis manufacturing cycle efficiency (MCE) since the production level is still low; (4) In the learning and growth prespective it can be carried out properly since it has been implemented in order to improve employeesâ capability by providing trainings and seminars to the whole employees evenly. It can be evaluated from the four prespective that PT Aweco Indosteel Perkasa Surabaya performance indicator is already quite well. Keywords: Performance Measurement, Balanced Scorecard, Return On Investment and MCE